2011
DOI: 10.1167/iovs.10-5957
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of Vacuolar Protein Sorting 11 (vps11) Causes Retinal Pathogenesis in a Vertebrate Model of Syndromic Albinism

Abstract: PURPOSE.To establish the zebrafish platinum mutant as a model for studying vision defects caused by syndromic albinism diseases such as Chediak-Higashi syndrome, Griscelli syndrome, and Hermansky-Pudlak syndrome (HPS). METHODS. Bulked segregant analysis and candidate gene sequencing revealed that the zebrafish platinum mutation is a single-nucleotide insertion in the vps11 (vacuolar protein sorting 11) gene. Expression of vps11 was determined by RT-PCR and in situ hybridization. Mutants were analyzed for pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…Fine mapping analysis, narrowed the region to 53kilobases, containing the ift46 , vps11 and hyou1 genes (Figure 2A). Previous studies examining vps11 medaka and zebrafish ( platinum ) mutants indicated hypopigmentation phenotypes very similar to the integrity mutant [10], [11]. Based on these previous findings, we sequenced the vps11 gene in mutant larvae.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Fine mapping analysis, narrowed the region to 53kilobases, containing the ift46 , vps11 and hyou1 genes (Figure 2A). Previous studies examining vps11 medaka and zebrafish ( platinum ) mutants indicated hypopigmentation phenotypes very similar to the integrity mutant [10], [11]. Based on these previous findings, we sequenced the vps11 gene in mutant larvae.…”
Section: Resultsmentioning
confidence: 75%
“…The following alleles were used: vps11 w66 , kit w34 [15] and WIK for mapping. platinum zebrafish were used for complementation and zVAD-fmk melanophore quantification analysis [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth spaced cysteine residue is the mutated residue in our patients. Loss of Vps11 in zebrafish manifests by oculocutaneous albinism, pericardial oedema, hepatomegaly and premature death underscoring Vps11 role in the fish melanosome maturation 20. Studies in various yeast mutants revealed that Vps11 is an essential component of the endosomal system;21 vps11 Δ null mutants exhibited defects in endosomal and vacuolar delivery and in late endosome and vacuole fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Here we benefited from previous work that identified several mutants in genes encoding members of the HOPS (homotypic fusion and vacuole protein sorting) complex and V-H + -ATPase complexes. [7][8][9] We found that both the HOPS complex genes vps11 and vps18, Another area of interest is investigating how vacuole expansion and final size are determined. The rigid ECM encasing the notochord ultimately restricts the expansion of the single vacuole within inner cells.…”
Section: Cellular Architecture: What Makes a Single Vacuole More Effimentioning
confidence: 95%